Roadmap for Restarting Elective Surgery During/After COVID-19 Pandemic - Sharma, Dhananjaya (Indian J Surg, 2020)
The worldwide COVID-19 pandemic has resulted in complete stoppage of elective surgery in most countries, which has created a huge backlog of waiting patients. This invited editorial comments on the current challenge of restarting elective surgery during/after COVID-19 pandemic.